Effects of transcranial magnetic stimulation on glial cells: An integrative review: Glía y estimulación magnética - Verdugo Díaz, Leticia; Acosta-Luna, Rodrigo (Horizonte Sanitario, 2024)
Objective: To identify the main effects of repetitive type transcranial magnetic (rTMS) and theta burst (TBS) stimulation on glial cells such as astrocytes, microglia, and oligodendrocytes in animal models of different nervous system pathologies.Material and methods: An integrative review was carried out in the Pubmed, Web of Science, EBSCO, and Cochrane databases published between 1995 and July 2022. We selected works that will use only rTMS and TBS configurations. The Boolean logical descriptors and operators AND, and OR were combined with the following words: “transcranial magnetic stimulation, glial cells/ astrocytes/ oligodendrocytes/ microglia”.Results: Twenty-seven works were obtained, of which 81% were in vivo studies and the rest are works carried out in vitro, in which different models of pathologies are used. More than 80% of the works focus on reporting astrogliosis through the GFAP marker, while another 41% investigate what happens in the microglia with the Iba-1 marker, and only 9% of the investigations focus on oligodendrocytes at least in vivo studies.Conclusions: The main effects reported of rTMS, and TBS was the decrease in glial and astroglial reactivity.  This decrease could be due to interaction among astrocytes, microglia, oligodendrocytes, and neurons, which would lead to a recovery in different CNS pathologies. Keywords: Astrocytes; Microglia; Oligodendrocytes; Inflammation.